2021
DOI: 10.1177/0954407020987829
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigation on the heat transfer of an automotive engine’s turbocharger

Abstract: Measuring the temperature distribution in a complex and important engine part, such as a turbocharger, is essential for improving engine performance and efficiency. Heat transfer from the turbine to the compressor can strongly influence the turbocharger performance. One of the main measurement methods involves the installation of multiple K-type sensors. However, the location as well as the maximum and minimum temperatures of the turbocharger and the subsequent critical points may not be obtained by using sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Basir et al [14] used thermocouples and an infrared camera to study the temperature distribution of the TCR housing in engines. They found that the temperature of the bearing housing near the turbine housing is higher than the area adjacent to the compressor body.…”
Section: Introductionmentioning
confidence: 99%
“…Basir et al [14] used thermocouples and an infrared camera to study the temperature distribution of the TCR housing in engines. They found that the temperature of the bearing housing near the turbine housing is higher than the area adjacent to the compressor body.…”
Section: Introductionmentioning
confidence: 99%
“…Turbine housing -a key part of the turbocharger -generates thermomechanical fatigue under the influence of high-temperature gas and engine vibrations. [1][2][3] Hence, the thermomechanical fatigue of turbochargers has become a concern in the design of turbochargers.…”
Section: Introductionmentioning
confidence: 99%